The determinants and concept of effective implementations of ECM systems - Wójtowicz, Radosław (Determinanty i koncepcja efektywnego wdrażania systemów klasy ECM, 2021)
The article describes the main factors which directly or indirectly influence the range and pace of IT implementation projects. It analyses the main structural elements and functional procedures of the implementation reengineering in the ECM (Enterprise Content Management) systems area, and presents the outline of managing projects execution. The main objective of this paper is to present the author’s general conceptual model of the implementations of the ECM system in an organization, resulting from the preliminary literature review and extensive practical experience.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 4 (62), s. 82-93
Keywords: IT projects; IT systems implementations; ECM system; projekty informatyczne; wdrażanie systemów informatycznych; systemy klasy ECM